Ca[2+]-calpains axis regulates Yki stability and activity in Drosophila. - Zhai, C.; Wang, Y.; Qi, S.; Yang, M.; Wu, S. (Journal of Genetics and Genomics [Yi chuan xue bao], 2024)
Yorkie (Yki) is a key effector of the Hippo pathway that activates the expression of targets by associating with the transcription factor Scalloped. Various upstream signals, such as cell polarity and mechanical cues, control transcriptional programs by regulating Yki activity. Searching for Yki regulatory factors has far-reaching significance for studying the Hippo pathway in development and human diseases. In this study, we identify Calpain-A (CalpA) and Calpain-B (CalpB), two calcium (Ca[2+])-dependent modulatory proteases of the calpain family, as critical regulators of Yki in Drosophila that interact with Yki, respectively. Ca[2+] induces Yki cleavage in a CalpA/CalpB-dependent manner, and the protease activity of CalpA/CalpB is pivotal for the cleavage. Furthermore, overexpression of CalpA or CalpB in Drosophila partially restores the large wing phenotype caused by Yki overexpression, and F98 of Yki is an important cleavage site by the Ca[2+]-calpains axis. Our study uncovers a unique mechanism whereby the Ca[2+]-calpain axis modulates Yki activity through protein cleavage.